Consumerism Culture and its Impact on Employees’ Work Effectiveness: The Case of a National Government Agency in the Philippines - Jarick Mar P Gubi; Mary Jane N Morales; Jesus P Briones (International Journal of Entrepreneurship, Business, and Creative Economy, 2024)
The workplace environment is not spared by how consumerism culture (CC) influences the transformation of individual lifestyles and aspirations. This study investigated the impact of CC on the employees’ work effectiveness of the subject national government agency (NGA) in the Philippines. This descriptive-quantitative research used a structured questionnaire to cover the impact of CC on the four dimensions of work effectiveness: work attitude, individual well-being, environmental sustainability, and social connections of employees within the organization. The data were gathered from 109 employees of the subject NGA. The study found that among the dimensions of work effectiveness, only environmental sustainability appeared to be affected by CC. Moreover, the study conducted within the context of the subject NGA revealed that there is no statistically significant relationship between CC in terms of employees’ shopping frequency and their perceptions of product or service brand reputation, and the four key dimensions of work effectiveness. This finding indicates that CC, as represented by these variables, does not significantly impact the critical aspects of employees’ work effectiveness within the organization. This study can serve as baseline information for developing a comprehensive employee development program for enhancing work effectiveness and fostering a healthier workplace culture among the prevailing consumerism trends in society.